Consensus recommendations for COVID-19-related myocarditis in athletes: proof of concept—case report. Issue 2 (27th January 2023) - Abdelfattah, Omar M; Mathur, Tarun; Martinez, Matthew W
Abstract: Background: Post-viral myocarditis has been associated with sudden cardiac death in athletes. Since the beginning of the COVID-19 pandemic, the concern of post-viral myocarditis impacting the professional athletic community has been present. Case summary: An elite-level basketball player presented after a positive COVID-19 test with findings consistent with ventricular tachycardia related to myocardial fibrosis/scar from a COVID-19-related myocarditis. Although rare, COVID-19 myocarditis can occur. This case illustrates how the consensus guidelines for return-to-play correctly identified the player as high risk with appropriate downstream evaluation by cardiac magnetic resonance (CMR) imaging. The stepwise approach is illustrated in this case and highlights the utility and success of the algorithm when approaching athletes with COVID-19-related myocarditis risk and determining a return to exercise. Discussion: Diligence is required to identify competitive athletes with features suggestive of myocarditis at the initial presentation and with the return to exercise. Cardiopulmonary symptoms in the setting of recent COVID-19 infection should prompt additional testing in a stepwise fashion and often benefit from CMR in addition to the triad testing with electrocardiography, echocardiography, and cardiac troponin measurement to further investigate clinical presentations of COVID-19-related myocarditis. Graphical Abstract: Graphical abstract Stepwise approach to the evaluation of myocarditis in athletes.